2022
DOI: 10.1371/journal.pone.0268272
|View full text |Cite
|
Sign up to set email alerts
|

Access to and challenges in water, sanitation, and hygiene in healthcare facilities during the early phase of the COVID-19 pandemic in Ethiopia: A mixed-methods evaluation

Abstract: Background Inadequate water, sanitation, and hygiene (WASH) in healthcare facilities (HCFs) have an impact on the transmission of infectious diseases, including COVID-19 pandemic. But, there is limited data on the status of WASH facilities in the healthcare settings of Ethiopia. Therefore, this study aimed to assess WASH facilities and related challenges in the HCFs of Northeastern Ethiopia during the early phase of COVID-19 pandemic. Methods An institution-based cross-sectional study was conducted from July… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 39 publications
0
20
1
Order By: Relevance
“…The basic access to water service (86%) was higher than from national level access (30%) (18), and the worldwide level of basic water service (78%) (6). However, the available basic sanitation service(0%) and basic hand hygiene service (8.1%) in our study were lower than from national level of access 59% and 52% respectively by 2016 (18), and from the study conducted in the north western part of Ethiopia, 21.4% of facility had basic access to hand washing facility (23). The higher level of basic water service access might be attributed to the study area conducted in urban setting, which is the capital city of Ethiopia with better investment to access improved water sources as compared to studies conducted in urban and rural parts of the country.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…The basic access to water service (86%) was higher than from national level access (30%) (18), and the worldwide level of basic water service (78%) (6). However, the available basic sanitation service(0%) and basic hand hygiene service (8.1%) in our study were lower than from national level of access 59% and 52% respectively by 2016 (18), and from the study conducted in the north western part of Ethiopia, 21.4% of facility had basic access to hand washing facility (23). The higher level of basic water service access might be attributed to the study area conducted in urban setting, which is the capital city of Ethiopia with better investment to access improved water sources as compared to studies conducted in urban and rural parts of the country.…”
Section: Discussioncontrasting
confidence: 70%
“…In the context of poor healthcare WASH services, adverse events including healthcare acquired infection and risk of AMR significantly affect the healthcare system (23). In our study, built environments of WASH infrastructure was found to be the most commonly cited barrier to WASH services provision in all healthcare facility.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“… 9 , 10 Due to their poor health infrastructure and training, African countries are more vulnerable to the spread of disease. 11 Additionally, their inability to quickly receive the vaccination raises the danger of disease spread. 12 Vaccination programs for Africans may be further delayed by vaccine-related expenses and transfer problems until late 2021 or early 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Inadequate WASH, malnutrition and infectious diseases are intricately linked [27]. While malnutrition is directly associated with insufficient dietary intake, underlying contributing factors, such as lack of access to safe and adequate WASH, result in recurrent infectious diseases such as intestinal parasites, diarrhea and COVID-19 [28,29]. The intestinal parasites interfere with the digestive process by inhibiting the absorption of nutrients leading to compromised immunity of the host [27].…”
Section: Introductionmentioning
confidence: 99%